Implementasi Media Permainan Ular Tangga Terhadap Hasil Belajar IPA Pada Materi Siklus Air Kelas V SDN 31 Cakranegara - Fidhea Aisara; I Ketut Widiada; Muhammad Syazali (Journal of Classroom Action Research, 2023)
This study aims to determine the effectiveness of the implementation of snakes and ladders game media on science learning outcomes in Class V water cycle material at SDN 31 Cakranegara. This type of research is experimental research using the Pre-Experimental design of the One Group Pretest-Posttest type. The research instrument used was a written test in the form of multiple choices. Before conducting an assessment of the hypothesis, a requirement test is carried out, namely the normality test. The normality test results obtained a significance value for the pretest data of 0.200 > 0.05 and a posttest significance value of 0.153 > 0.05 which means that the data is normally distributed. Once it is known that the data are normally distributed, a hypothesis test is carried out using the paired simple t-test with a value of 000 <0.05. This states that Ho is rejected and Ha is accepted, which means that there is a difference in learning outcomes between before and after being given the snakes and ladders media game treatment. science lesson about the water cycle for class V SDN 31 Cakranegara